Product liability and protection of EU consumers: is it time for a serious reassessment?. (2nd January 2019) - Risso, Giorgio
Abstract : The European Union (EU) has not enacted a coherent and fully-fledged product liability regime. At the substantive level, the Product Liability Directive – adopted in 1985 – is the only piece of legislation harmonising the laws of the Member States. At the private international law level, the special choice-of-laws provision in the Rome II Regulation coexists with the general rules in the Brussels I-bis Regulation. Cross-border product liability cases are therefore subject to different pieces of legislation containing either "general" or "specific" provisions. In turn, such general and specific provisions do have their own rationales which, simplistically, can be inspired by "pro-consumer", "pro-producer", or more "balanced" considerations, or can be completely "indifferent" to consumer protection. This article examines the interactions between the Directive, the Rome II and the Brussels I-bis Regulations in cross-border product liability cases. The aim of this article is to assess whether the piecemeal regime existing at the EU level risks undermining the protection of EU consumers. The analysis demonstrates that the regime is quite effective in guaranteeing an adequate level of consumer protection, but reforms are needed, especially to address liability claims involving non-EU manufacturers or claims otherwise connected to third States, without requiring a complete overhaul of the EU product liability regime.